Pemanfaatan Aplikasi Untuk Memberikan Diagnosa Awal Penyakit Gigi Dan Mulut Pada Ins Dental Care - Rini Sovia; Ricki Ardiansyah; Maha Rani (STMIK Royal, 2024)
Technological developments in various fields continue to increase, one of which is in the health sector, namely the use of applications to provide initial diagnoses of dental and oral diseases. Lack of public awareness and knowledge in maintaining oral health can give rise to various kinds of diseases, some of which can be cured with proper treatment. One way that can be done to prevent this disease is by providing education to the public by using a web-based application. The PKM team held activities at Ins Dental Care. The method used in this activity is training in the use of applications for early diagnosis of dental and oral diseases with the participants being doctors and nurses. The aim of this service activity is to provide knowledge to participants about applications that can be used by participants to provide initial diagnoses of dental and oral diseases so that later participants can easily obtain information about dental and oral diseases. With this application, Ins Dental Care can easily provide education to the public about dental health and reach local communities to provide education about dental health and dental disease. By utilizing a web application for early diagnosis of dental and oral diseases, people can obtain information on diagnosing dental diseases independently without having to come to the clinic. Keywords: training; application; diagnosis; dental and oral diseases